The effects of hydrocortisone and yohimbine on human behavior in approach-avoidance conflicts - Fricke, Kim; Alexander, Nina; Jacobsen, Thomas; Krug, Henriette; Wehkamp, Kai; Vogel, Susanne (Psychopharmacology, 2023)
Rationale Balancing approach of positive and avoidance of negative stimuli is essential when faced with approach-avoidance conflicts, e.g., situations with both positive and negative outcomes. This balance is disturbed in several mental disorders, e.g., excessive avoidance in anxiety disorders, and heightened approach in substance use disorders. Since stress is assumed to impact these disorders’ etiology and maintenance, it seems crucial to understand how stress influences behavior in approach-avoidance conflicts. Indeed, some studies suggested altered approach-avoidance behavior under acute stress, but the mechanism underlying these effects is unknown. Objectives Investigate how the pharmacological manipulation of major stress mediators (cortisol and noradrenaline) influences task-based approach-avoidance conflict behavior in healthy individuals. Methods Ninety-six participants (48 women, 48 men) received either 20mg hydrocortisone, 20mg yohimbine, both, or placebo before performing a task targeting foraging under predation in a fully crossed double-blind between-subject design. Moreover, we investigated effects of gender and endogenous testosterone and estradiol levels on approach-avoidance behavior. Results While biological stress markers (cortisol concentration, alpha amylase activity) indicated successful pharmacological manipulation, behavior in approach-avoidance conflicts was not affected as expected. Although yohimbine administration affected risky foraging latency under predation, we found no main effect of hydrocortisone or their interaction on behavior. In contrast, we found gender differences for almost all behavioral outcome measures, which might be explained by differences in endogenous testosterone levels. Conclusions The investigated major stress mediators were not sufficient to imitate previously shown stress effects on approach-avoidance conflict behavior. We discuss potential reasons for our findings and implications for future research.